2019
DOI: 10.1002/app.47598
|View full text |Cite
|
Sign up to set email alerts
|

Production and investigation of structure and properties of polyethylene–polylactide composites

Abstract: Under conditions of shear deformations, low‐density polyethylene (LDPE) and polylactide (PLA) composites are obtained in rotor disperser. The production of these composites allows one to use polymers derived from natural raw and to reduce the cost of the materials on their base. The addition of rigid PLA leads to increase in elastic modulus from 200 for LDPE to 1190 for LDPE–PLA (50:50 wt %) composites and in tensile strength from 13.3 for LDPE to 17.8 for LDPE–PLA. By differential scanning calorimetry method,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
2
6
0
1
Order By: Relevance
“…The mechanical parameters of the LDPE–PLA–starch ternary blends under investigation and similar characteristics of the LDPE–starch, [ 12 ] LDPE–PLA, [ 15 ] and PLA–starch [ 25 ] binary blends previously obtained are presented in Table 1. As can be seen, the addition of such rigid polymers as PLA and starch to LDPE leads to an increase in the elastic modulus E , 1190 MPa in the case of LDPE–starch (50:50 wt%).…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…The mechanical parameters of the LDPE–PLA–starch ternary blends under investigation and similar characteristics of the LDPE–starch, [ 12 ] LDPE–PLA, [ 15 ] and PLA–starch [ 25 ] binary blends previously obtained are presented in Table 1. As can be seen, the addition of such rigid polymers as PLA and starch to LDPE leads to an increase in the elastic modulus E , 1190 MPa in the case of LDPE–starch (50:50 wt%).…”
Section: Resultsmentioning
confidence: 79%
“…Authors showed in ref. [12,25,15] when studying the LDPE-starch, PLA-starch, and LDPE-PLA blends that mechanical properties and biodegradability depend on the component ratio both for the LDPE blends with natural polymers and blends based on two polymers of natural origin. Based on present knowledge, the LDPE blends with polysaccharide starch with addition of a second polymer of natural origin PLA were obtained and studied in this work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past 20 years, PLA has received increasing attention due to its biodegradability, low gas emission, and low toxicity in food packaging applications (Arslan & Dilsiz, 2020; Trongsatitkul & Chaiwong, 2017). The most important feature of PLA, which is of industrial importance, is that it can be processed by conventional plastic processing instruments (DeGruson, 2016; Rogovina et al., 2019). PLA is used in electrospinning process of Ch to make an antibacterial coating of PLA/Ch nanofiber on the surface of low‐density polyethylene (LDPE)/PLA composite films.…”
Section: Introductionmentioning
confidence: 99%